THE USE OF TICS ON THE ADUANAS, AND SUNAT WEBSITE - Vergara Moncada, Raúl Jesús (2009)
Today we live in the information age where private and public institutions are using new information and communication technologies in which the Tax Administrations in the world with the help of the Inter-American Development Bank (IDB) and the Technical Advisory International Cooperation with the Inter-American Center of Tax Administrations (CIAT) are in the process of modernization of various services offered On_Line Taxpayer using these new tools, in the case of Peru has a Sunat Tax Portal (Internal taxation), which is merged with Customs since 2002 and which offer greater comfort for the user now can pay taxes from the comfort of your home, office or company in this paper, we consider the Sunat institution as an entity that exploits these resources technological platform to provide its Essalud, ONP and currently the Ministry of Labor through the spreadsheet, its origins and objectives, description of services, planning and implementation phases, total investment and costs of implementing the new Information and Communication Technologies and finally the impact and results.